Pengaruh Literasi Digital dan User Interface Terhadap Keputusan Pembelian dengan Perceive Ease of Use Sebagai Variabel Intervening pada Pengguna Acces By Kai Generasi Milenial dan Z di Kabupaten Pasuruan - Sinta Hardianti; Kholid Murtadlo (MES Bogor, 2025)
This study aims to determine the optimal digital literacy possessed by Acces by KAI users and the user interface on train ticket purchase decisions with perceived ease of use as an intervening variable for Millennial and Z Generation Acces by KAI Users in Pasuruan Regency. The sampling technique used is a non-probability sampling method with a puposive sampling sub-technique with a total of 96 respondents. respondents obtained from online questionnaires covering respondents in Pasuruan Regency. This research method uses quantitative methods by analyzing data using descriptive analysis techniques and Path Analysis tests with the help of SPSS version 22. From the results of the study it can be concluded that from the results of the t test, Digital Literacy has a positive and significant effect on Perceive Ease Of Use, User Interface has a positive and significant effect on Perceive Ease Of Use, Digital Literacy has a positive and significant effect on Purchasing Decisions, User Interface has no effect on Purchasing Decisions, Perceive Ease Of Use has a positive and significant effect on Purchasing Decisions. Based on the Sobel Test, Digital Literacy affects Purchasing Decisions through Perceive Ease Of Use as an intervening variable, User Interface affects Purchasing Decisions through Perceive Ease Of Use as an intervening variable.